P-118 Fecal Microbiota Transplantation via Colonoscopy is Safe and Effective in Active Ulcerative Colitis. (February 2017) - Jacob, Vinita; Crawford, Carl; Cohen-Mekelburg, Shirley; Schneider, Yecheskel; Chabouni, Fatiha; O'Neil, Sarah; Bosworth, Brian; Viladomiu, Monica; Ajami, Nadim; Petrosino, Joseph; Artis, David; Scherl, Ellen; et al.
Abstract : Background: Ulcerative colitis (UC) is frequently refractory to conventional medical therapy and new strategies are needed to induce remission. Fecal microbiota transplantation (FMT) is an alternate therapeutic strategy, which has been reported to improve remission rates when delivered via enema without significant adverse effects. To evaluate the safety and therapeutic efficacy of colonoscopic FMT for active UC, we performed an open-label, pilot study of 20 patients with non-infectious, active UC using a 2-donor fecal microbiota preparation (FMP) to enhance the biodiversity of the transplanted material. Methods: Patients with active UC (Mayo Score ≥3 and endoscopic subscore ≥1) were recruited from the Jill Roberts IBD Center. Twenty patients with stool samples negative for C. difficile and conventional gastrointestinal pathogens were enrolled. FMT was performed by colonoscopic delivery of a single 120 mL infusion of a 2-donor FMP concentrate (provided by OpenBiome) into the ileum and right colon. The primary outcome was clinical response (defined by a change in Mayo score ≥ 3 and a bleeding subscore ⩽1) at week 4. Secondary endpoints included remission of UC (defined by a Mayo score ⩽2 and no subscore >1) and mucosal healing (defined by an endoscopy subscore of 0) at week 4. Patients provided stool samples for microbiome analysis before and at week 2 and 4 following FMT. Results: All 20 patients completed clinical and endoscopic evaluation at week 4. No serious adverse events were noted. Seven patients (35%) achieved the primary outcome of clinical response by week 4. Three patients (15%) were in remission at week 4 and 2 of these patients (10%) achieved mucosal healing. Three patients (15%) required escalation of care (anti-TNFa therapy, N = 2; colectomy, N = 1). 16S rRNA analysis revealed that FMT significantly increased the recipient's microbial diversity ( P = 0.001, Mann-Whitney) and that community composition at week 2 and week 4 was more similar to the donor FMP than recipient at baseline (PERMANOVA, P = 0.001). Conclusions: Colonoscopic FMT using a 2-donor FMP is safe and effective in achieving clinical response by week 4 in patients with active UC. Longer-term follow up and correlation with microbial parameters will provide insight into factors influencing clinical outcome.